STRATEGI PEMBELAJARAN BERBASIS BLENDED LEARNING PADA PROGRAM STUDI PENDIDIKAN IPS FIS UNNES - Aisyah Nur Sayidatun Nisa; Asep Ginanjar (Universitas Muria Kudus, 2024)
The aim of this research is to find out what kind of support the Social Sciences Education Study Program provides as a policy maker in implementing blended learning-based learning strategies; to find out the extent of the use of blended learning-based technology in the FIS UNNES Social Sciences Education Study Program; to analyze the implementation of blended learning-based learning strategies in the FIS UNNES Social Sciences Education Study Program. The research method used is descriptive with a qualitative approach. The research subject is the academic community of the Social Sciences Education Study Program. Data collection through interviews, observation and documentation with data validity testing using triangulation methods and data analysis techniques using interactive analysis. The results of the research found that the blended learning-based learning strategy in the FIS UNNES Social Sciences education study program was running well. Support from lecturers, students, study program coordinators, faculties and universities really supports the implementation of this. One of the existing policies is the curriculum and supporting infrastructure.